Quantifying Musculoskeletal Strain in Laptop Users with Laplace Transformation and Delay Differential Equations - Bhardwaj, Piyush; Dipesh, (Journal of Environmental Accounting and Management, 2026)
The Musculoskeletal problems have become increasingly common worldwide, accounting for 2% of the overall illness burden. Cumulative trauma disorders (CTD) and repetitive strain injuries (RSI) are two ailments that frequently cause headaches, neck and wrist discomfort, and backache, especially among office workers and students. This study investigates the incidence of work-related RSI and musculoskeletal diseases (MSDs) among laptop users using delay differential equation, focusing on the influence of physical workplace characteristics such as prolonged static muscle stress and poor yard arrangement. The delay parameter is used to assess the musculoskeletal impact on laptop users. The Laplace transformation and hopf-bifurcation is examined about the non-zero equilibrium point. Furthermore, stability is examined. The research confirms that physical factors like postural change and repetitive strain leading to degenerative changes significantly contribute to MSD development in laptop users. The findings emphasize the need for improved ergonomic practices to mitigate the rising trend of musculoskeletal disorders in the digital age. MATLAB is used to draw the graphical representation of the model.